Early Prediction of Preeclampsia: The Role of Doppler Ultrasound in Improving Maternal and Fetal Outcomes - Tarifi, Ayman Othman; Akhtar, Nafees; Atito, Ayman; Ayman, Ahmad (Journal of Fatima Jinnah Medical University, 2024)
Background: Early identification of Doppler abnormalities allows for closer monitoring, early intervention, and tailored management strategies to mitigate the severity of preeclampsia and its complications particularly in high-risk pregnancies, those with a history of preeclampsia or other risk factors. This study aimed to evaluate the efficacy of uterine artery Doppler ultrasound in predicting preeclampsia during the first trimester and its impact on maternal and fetal outcomes. Patients and Methods: A prospective cohort study was conducted with 150 pregnant women between 11-14 weeks of gestation. Uterine artery Doppler ultrasound was performed to measure pulsatility index (PI), resistance index (RI), and the presence of an early diastolic notch. Patients were followed throughout pregnancy to assess the development of preeclampsia. Maternal and fetal outcomes were recorded, including preterm birth, low birth weight, NICU admissions, and maternal complications. Results: Of the 150 participants, 25 (16.6%) developed preeclampsia. Abnormal Doppler findings were significantly associated with the development of preeclampsia, with a sensitivity of 80% and specificity of 84%. The negative predictive value was 96%, indicating effective early risk stratification. Patients with early detection had fewer cases of severe preeclampsia (40% vs. 60%, p < 0.05), fewer preterm births (12% vs. 28%, p = 0.04), and reduced NICU admissions (10% vs. 25%, p < 0.05) compared to those without early detection. Maternal ICU admission was also lower in the Doppler abnormality group (2% vs. 10%, p < 0.05). Conclusion: Early prediction of preeclampsia using uterine artery Doppler ultrasound allows for timely interventions, significantly improving maternal and fetal outcomes by reducing the severity of preeclampsia and associated complications. Incorporating this non-invasive screening tool into routine antenatal care can enhance pregnancy management and lower the risks of adverse events.